Analisa Kebutuhan Air Bersih dan Kapasitas Tampungan Reservoir di Desa Prangat Baru Kecamatan Marang Kayu - Kresensia Monica Sonia Kelawing Kinam; Suharto Suharto; Findia Findia (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze clean water demand and the required reservoir storage capacity in Prangat Baru Village, Marang Kayu District. The urgency of this research arises from continuous population growth that increases water demand, while the existing clean water supply system has not been optimally managed. This research applies a descriptive quantitative approach. Primary data were obtained through field surveys, while secondary data were collected from village population records and supporting literature. Population projection was conducted using the arithmetic method, assuming a linear population growth pattern during the planning period. The results show that the population of Prangat Baru Village is projected to reach 620 people by 2030, with an average annual growth rate of approximately 3%. Based on the rural clean water consumption standard of 50 liters per capita per day, total clean water demand in 2030 is estimated at 30.99 m³ per day. The analysis indicates that the existing reservoir capacity is insufficient to meet the projected demand. Conversely, the planned reservoir with a storage capacity of 31.43 m³ is considered more effective in ensuring continuity and reliability of clean water supply. The planned reservoir is designed in a cylindrical form with a height of 2.5 m, a radius of 2 m, and a diameter of 4 m. Overall, the findings emphasize that accurate population projection and appropriate reservoir capacity planning are essential to support a sustainable rural clean water supply system and ensure equitable, reliable, year-round water services for the community in future.